Simulated annealing algorithm to solve Aircraft Landing Problem - Boukraa, Samah; Hemmak Allaoua: Supervisor (Mohamed Boudiaf University of M'sila, 2024)
In this work, we solved the problem of airplane landing, using the simulated annealing algorithm. This problem is known as NP-hard problem, which means that finding an ideal solution in a reasonable period of time is a challenge. This algorithm we applied allowed us to efficiently explore the solution space and get good results. Our solutions may not be ideal but they were close to the satisfactory level within a reasonable time frame. The simulated annealing algorithm has made great progress in solving the problem of aircraft landing and has opened up new avenues for research and improvement.
Keywords: ALP; Combinatorial Optimization; Simulated annealing; Metaheuristics